2022
DOI: 10.1073/pnas.2203083119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nuclear quantum effects on the electronic properties of amorphous carbon

Abstract: We carry out quantum simulations to study the physical properties of diamond-like amorphous carbon by coupling first-principles molecular dynamics with a quantum thermostat, and we analyze multiple samples representative of different defective sites present in the disordered network. We show that quantum vibronic coupling is critical in determining the electronic properties of the system, in particular its electronic and mobility gaps, while it has a moderate influence on the structural properties. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Many works have shown substantial NQEs in hydrogen-containing systems associated with quantum tunneling of protons and zero-point motion of chemical bonds involving hydrogen atoms. For example, NQEs modulate hydrogen bond interactions. , Given the strong correlation between motions of the organic and inorganic components of HOIPs, including hydrogen bonding, one can expect that NQEs influence HOIP geometric and electronic properties as well as charge carrier dynamics. Typically, NQEs are more pronounced at low than high temperatures because high temperatures put systems in the classical limit. HOIP solar cells and other devices operate at different temperatures, and therefore it is important to study NQEs over a temperature range. In this regard, the tetragonal phase of MAPbI 3 is an excellent system to study the temperature-dependent influence of NQEs on the geometric and electronic properties of HOIPs and the nonradiative electron–hole recombination dynamics because the phase remains stable in the range between 160 and 330 K, including both low and ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have shown substantial NQEs in hydrogen-containing systems associated with quantum tunneling of protons and zero-point motion of chemical bonds involving hydrogen atoms. For example, NQEs modulate hydrogen bond interactions. , Given the strong correlation between motions of the organic and inorganic components of HOIPs, including hydrogen bonding, one can expect that NQEs influence HOIP geometric and electronic properties as well as charge carrier dynamics. Typically, NQEs are more pronounced at low than high temperatures because high temperatures put systems in the classical limit. HOIP solar cells and other devices operate at different temperatures, and therefore it is important to study NQEs over a temperature range. In this regard, the tetragonal phase of MAPbI 3 is an excellent system to study the temperature-dependent influence of NQEs on the geometric and electronic properties of HOIPs and the nonradiative electron–hole recombination dynamics because the phase remains stable in the range between 160 and 330 K, including both low and ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, recently, the validity of the harmonic approximation has been questioned in the case of perovskites, 19 organic molecular crystals, 14 and amorphous carbon. 15 The stochastic method is an interesting alternative to the FP technique, especially the so-called one-shot implementation 20,21 proposed by Zacharias et al Using such a method, Monserrat et al reported very large (1−2 eV) zero phonon renormalizations (ZPR) of the fundamental gap of molecular crystals composed of small molecules: CH 4 , NH 3 , H 2 O, and HF, and discussed the limitations of the quadratic approximation within the FP method. 12 Using path-integral molecular dynamics simulations and a machine-learned potential, Alvertis et al showed that the harmonic approximation, which underlies both the stochastic and FP methods, fails catastrophically for acene molecular crystals, 14 and their results challenged the validity of the stochastic method, at least for some molecular crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum vibronic effects play an important role in determining the temperature dependence of the electronic properties of molecules and solids, including their fundamental electronic gaps, as reported for small molecules, , nanoclusters, and crystalline and amorphous solids . Hence, predicting quantum vibronic effects is critical to understanding the physical behavior of systems used in applications ranging from bioelectronics, thermoelectrics, and photovoltaics, to optical fiber technologies, spintronics, and quantum sensing.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that the quantum fluctuations exhibited by them, either by the light ones like H or heavier ones like C and O, strongly influence the properties of many materials and different physical processes. [29][30][31][32][33] Nuclear quantum effects (NQEs) in DPT are typically manifested through zero-point energy and tunnelling. While the zero-point energy fluctuations usually affect free energy barriers, tunnelling facilitates classically forbidden pathways at lower temperature.…”
Section: Introductionmentioning
confidence: 99%